Workload and innovative work behavior as determinants of job performance among academicians in TVET institutions - Darmansah, Darlina; Omar, Siti Nur Zahirah; Che Cob, Che Mohd Syaharuddin (International Journal of Accounting, Finance and Business, 2025)
Job performance is essential for achieving organizational goals, making it a key focus for scholars and HR practitioners. However, the factors influencing job performance and their underlying mechanisms require further investigation. This study proposes a framework to examine the relationships between workload, innovative work behaviour (IWB), and job performance among TVET academicians in Malaysia. Academicians are central to educational institutions, shaping knowledge, fostering innovation, and driving excellence. The National TVET Policy 2023 and the Twelfth Malaysia Plan highlight the need for skilled TVET educators to support Malaysia’s transition to Industry 4.0. Additionally, the Malaysia Education Blueprint 2015–2025 emphasizes improving TVET enrolment and graduate outcomes, which are directly linked to the performance of academicians who play a critical role in delivering quality education. The empirical studies suggest that both workload and IWB significantly impact job performance. This paper concludes that effective management of workload and fostering an innovative work environment are crucial to improving job performance among academicians in TVET institutions, ultimately contributing to the development of Malaysia’s education system.